TINDAK PIDANA KORUPSI ANGGARAN PENDAPATAN DAN BELANJA DAERAH KOTA MALANG (STUDI KASUS DI PENGADILAN TIPIKOR SURABAYA) - siskha comaria (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACT Along with the existence of regional autonomy, the decentralization of regional finances or the granting of autonomy in the management of the APBD resulted in high flexibility for regional officials. From here, the formulation of the development of the number of cases, factors, modus operandi, and sanctions given for the corruption in the APBD that occurred in Malang City in 2016-2020 is drawn 2. This study aims to find out what is discussed in the formulation of the problem. This research method is empirical juridical research with sociological juridical approach, case, and qualitative. The source of the data used in this research is the Surabaya Corruption Court. Data collection techniques with field surveys, interviews and documentation. Data analysis techniques by organizing the data. starting from the discussion of the Regional Revenue and Expenditure Budget for Malang City Changes in 2015 the chairman of the Malang City Regional People's Representative Council asked for money from the Mayor of Malang and he agreed to give money in return with the term